Illustrating the phaenomena : celestial cartography in antiquity and the Middle Ages - Dekker, Elly (Oxford University Press, 2013)
In this volume all extant celestial maps and globes made before 1500 are described and analysed. It also discusses the astronomical sources involved in making these artefacts in antiquity, the Middle Ages, the Islamic world and the European Renaissance before 1500.